Utilisation of Village Potential in Batu Ampar Sub-district, Tanah Laut Regency - Singgih Priono; Irawanto; M. Jamili; Bakhtiar; Heru Budhihanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
Village potential in the Batu Ampar sub-district has not been maximised. Therefore, research on village potential is very important. The purpose of the study was to look at the physical and non-physical potential of villages in Batu Ampar Sub-district. The results of this research can be a program for the development and welfare of the community. The research approach is qualitative, with key informants being the sub-district head and informants being the village head and community members. The results showed that the existing land potential has not been maximally utilised, such as there is no research and education forest, which is very important for the community to be used as a livestock location or agrotourism. Meanwhile, the non-physical potential of villages in the sub-district, such as the nature of gotong royong, social organisations, village officials, and apparatus, still exists but has begun to fade